Feminist and Intersectional Analysis of Healthcare and Gender Oppression in Alice Walker's Strong Horse Tea: A Feminist Literary Criticism - Hussain, Syed Muzamil; Zahra, Syeda Tehzeeb (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
The short story